Tragique familial et effet de série : de La Mariane à La Mort des enfants d’Hérode - Caroline Labrune (Etudes Epistémè)
Is La Mort des enfants d’Hérode (1639) truly a sequel to Tristan’s La Mariane (1637) ? It seems La Calprenède is right when he suggests that both tragedies should not be read separately. In both plays, Herod is indeed a paradoxical figure, who acts as a tyrant as well as a courageous and clever sovereign; and he is also quick to be moved when confronted to a woman’s tears. Without La Mariane, La Calprenède’s Herod would not exist. But one should not consider La Mort des enfants d’Hérode only as another Mariane: its tragical dimension is quite singular. La Calprenède’s Herod has indeed improved since he sentenced his wife to death; nevertheless, he falls back into his old ways when he sends his legitimate sons, Alexandre and Aristobule, to the scaffold because he trusts his bastard son, Antipatre. He thus yields to a melancholy state that leads him to a symbolical suicide, as occurs in La Mariane. Considering all this, we examine how, in La Mort des enfants d’Hérode, La Calprenède manages to create a retrospective common authorship with his famous predecessor.